Antibiotic-Modifying Activity and Chemical Profile of the Essential Oil from the Leaves of Cordia verbenacea DC. Issue 2 (4th March 2017) - Carvalho, Victória Regina de Alencar; Silva, Maria Karollyna do Nascimento; Aguiar, José Júnior Souza; Bitu, Vanessa de Carvalho Nilo; Costa, José Galberto Martins da; Ribeiro-Filho, Jaime; Coutinho, Henrique Douglas Melo; Pinho, Antonio Ivanildo; Fagner Ferreira Matias, Edinardo
Abstract: This study aimed to determine the chemical profile of the essential oil obtained from the leaves of C. verbenacea DC and to evaluate its antibiotic and antibiotic-modifying activity by the gaseous contact method of the essential oil and its major component. The essential oil was analyzed by GC-MS. Chemical analysis identified a predominance of sabinene (31.99%), β-caryophyllene (13.10%), bicyclogermacrene (11.06%), germacrene-D (7.44%) and (+) spathulenol (6.53%). The essential oil and sabinene exhibited no antibacterial activity according to the method used. Sabinene combined with all antibiotics showed synergism against S. aureus and the essential oil showed indifference when combined with aminoglycosides. We demonstrated that sabinene has statistically significant antibiotic-modifying activity against S. aureus, indicating this compound as a new alternative pharmaceutical source in fighting infections by Gram-positive bacteria.